Exploring the Influences of Cutting-Edge Technologies on Operational Efficiency, Productivity, and Financial Profitability in Afghanistan's Tourism Sector - Hakimi, Musawer; Fazil, Abdul Wajid; Hakimi, Faiz Mohammad; Najieb, Khairullah; Hakimi, Samer (PT. Riset Press International, 2024)
This comprehensive study investigates the transformative impact of cutting-edge technologies Block-chain, Artificial Intelligence (AI), Augmented Reality (AR), and the Internet of Things (IoT) on Afghanistan's tourism industry. Employing Structural Equation Modeling (SEM) and a purposive sampling method, data was collected from 21 tourism agencies and 79 stakeholders across diverse provinces. The mixed-methods approach, combining quantitative and qualitative data, ensures a holistic understanding of technology integration dynamics. Ethical considerations, encompassing informed consent and participant anonymity, were paramount. Empirical findings consistently reflect positive perceptions regarding the technologies' transformative influence. Descriptive statistics underscore their significant impact on operational efficiency, productivity, collaboration, and financial profitability in Afghanistan's tourism sector. One-Sample T-Tests confirm a statistically significant increase in collaboration with stakeholders, while also highlighting challenges in adopting advanced technologies. Contributing valuable insights, the study provides tailored recommendations for Afghan tourism, including strategic technology adoption, capacity building, public-private partnerships, cybersecurity prioritization, community engagement promotion, and continuous monitoring and evaluation. Bridging academia and industry, these recommendations offer practical guidance. In conclusion, this research not only advances theoretical understanding but also furnishes actionable strategies for tourism agencies to strategically leverage cutting-edge technologies in Afghanistan. The study advocates for ongoing research to explore evolving technologies and their sustained impact on the dynamic global tourism landscape, ensuring continuous adaptation and growth.